Syntactic islands - Boeckx, Cedric (Cambridge ; New York : Cambridge University Press, 2012)
"The phenomenon of the syntactic 'island' - a clause or structure from which a word cannot be moved - is central to research and study in syntactic theory. This book provides a comprehensive overview of syntactic islands. What are they? How do they arise? Why do they exist? Cedric Boeckx discusses the pros and cons of all the major generative accounts of island effects, and focuses the discussion on whether islands are narrowly syntactic effects, are due to interface factors or are 'merely' performance effects. Thanks to the diversity of island effects, readers are given a unique opportunity to familiarize themselves with all the major research styles and types of analysis in theoretical linguistics and have the chance to reflect on the theoretical implications of concrete natural language examples, allowing them to develop their own synthesis"--
Machine generated contents note: 1. Never such innocence again; 2. What is really all just a mirage?; 3. Why the ultimate solution is unlikely to be purely syntactic; 4. Priority to the interfaces; 5. A tribute to Ross.
Bibliografske bilješke: str. 139-168.
Kazalo.
Keywords: gramatika - opća i poredbena; sintaksa; minimalistička teorija; sintaktički otoci